(untitled) (Journal of the College of Basic Education, 2023)
An educational crisis usually appears when there is a lack of consistency between the educational systems and the environmentExternal, that is, the local community, at a time when the local community is keeping pace with the rapid and rapid changesIn the different fields of life, in addition to the continuous technical developments and technology, we find that the educational systemStanding unable to introduce the necessary changes as quickly as possible, causing the crisis.